A comparative study of shear design methods for straight and skew concrete slabs. (1st April 2020) - Lipari, Alessandro
Highlights: Main codes of practice and research on shear strength of concrete slabs are reviewed. Practical procedures are proposed on how to extend established shear design methods to skew slabs. The case studies of two skew bridge decks are presented. Some scatter is found across different design procedures. Predicted shear strengths of skew slabs are found to be significantly lower than experimental strengths. Abstract: The shear behaviour of concrete members has been long investigated; however, there is still no consensus on a single design approach. Shear failures are generally brittle, hence highly undesired. Failure modes are traditionally classified into one-way and two-way (punching) shear. Nevertheless, in concrete slabs intermediate cases are observed when a concentrated load is located close to the supports. These cases are not considered in most codes of practice, despite some investigative efforts conducted in recent years. Furthermore, knowledge about the shear behaviour of skew slabs is still limited. This paper reviews the shear design provisions of main codes of practice, as well as relevant research on concrete slabs subjected to concentrated loads close to supports. Procedures for extending the code provisions to the design of skew slabs are proposed. These are illustrated and validated through the case studies of two skew railway decks, one simply-supported and the other continuous. Some scatter is found across different codes of practice, broadly reflecting their predominant parameters. The procedures are also compared to the limited experiments on skew slabs available in the literature. It is found that the predicted shear strengths are considerably smaller than the experimental values. Unexpectedly, the experiments highlighted a modest influence of the reinforcement grid orientation, which confirms that the mechanisms underlying shear design in slabs still need to be fully understood.